Combined effects of seawater acidification and emerging contaminants on marine bivalves - Munari, Marco (Università degli studi di Padova, 2014)
Marine organisms are exposed to a wide range of anthropogenic substances, many of them considered as emerging contaminants due to their growing production and not well-known environmental impact. Among emerging contaminants, pharmaceuticals and personal care products are cause for increasing concern, being bioactive substances widely used in both human and veterinary medicine. Climate changes, such as ocean acidification, could have a powerful effect on pharmaceuticals by altering their environmental behaviour and exposure pathways, thus resulting in an increased toxicity. Furthermore, shifts in environmental parameters could alter marine organism susceptibility to these compounds. In this context, the combined effects of seawater acidification, as predicted in climate change scenarios, and emerging contaminants (the non-steroidal anti-inflammatory drug, NSAID, diclofenac and the metabolic activator caffeine) were investigated for the first time in the Mediterranean mussel Mytilus galloprovincialis and the Manila clam Venerupis philippinarum. In adults of both species, we evaluated haemocyte and oxidative stress parameters in order to highlight potential effects due to the combination of seawater acidification and exposure to diclofenac. Other two experiments were carried out to investigate whether the exposure to seawater acidification-diclofenac and acidification–caffeine may affect physiological responses and haemocyte parameters, respectively, in adults of M. galloprovincialis. A flow-through system was used to carry out a three-weeks exposure of the studied bivalves. In the first week, animals were exposed to three pH values (8.1, 7.7, 7.4) only. Thereafter, they were maintained for 7 and 14 days at the three experimental pH values and exposed simultaneously to environmentally relevant concentrations of diclofenac/caffeine (0, 0.05 and 0.5 μg/L). To analyzed haemocyte parameters [total haemocyte count (THC), haemocyte volume and diameter, Neutral Red uptake (NRU), haemocyte proliferation and lysozyme ...